Il perpetuum mobile del desiderio Cox di Christoph Ransmayr e la raffigurazione letteraria del cosmopolitismo settecentesco tra esotismo e vanità (Altre Modernità, 2019)
The article sets out to analyse Christoph Ransmayr’s latest novel Cox oder Der Lauf der Zeit (2016) in the light of recent criticism. The complex relationship between 18th-century cosmopolitanism and its fictional adaptation features prominently in the novel. Our focus is upon the making of characters’ identities, the literary and visual techniques of narration (especially intertextual allusions and ekphrasis), and the coalescence of time, decay and desire as displayed in the novel.